Psychological distress. The Neo-Pentecostal language as a trigger for personal revival and transforma-tion (Przegląd Religioznawczy – The Religious Studies Review, 2022)
Over the past decades, Neo-Pentecostalism has spread across the nations, mainly because of its strong emphasis on the so-called prosperity gospel and the promotion of supernatural phenomena. John Wimber, the founder of what came to be known as power evangelism, stressed the importance of signs and wonders, whereas Charles Peter Wagner, the father of New Apostolic Reformation (NAR), developed the concept of leadership and strengthened the position of the highly-efficient, entrepreneurial ministers working independently. These two figures contributed enormously to the contemporary religious marketplace; therefore, their ideas have successfully shaped the intra-community reality of various religious groups representing Charismatic Christianity. The principal objective of this study is to investigate the role the Neo-Pentecostal language combined with non-linguistic elements plays in one’s personal revival and transformation. The research concerns both Neo-Pentecostals and Pentecostal Catholics from Poland and Italy. The analysis is based on participant observation, in-depth interviews, and surveys.